Geospatial perspective for monitoring SDG 6.6.1 based on spatial and temporal analysis of lake water storage variations in Dongting Lake, China - Huanhua Peng; Zihan Tang; Zhiming Chen; Yating Wu; Yuan Yuan; Qian Shi; Lelin Li; Hao Chen (Journal of Hydrology: Regional Studies)
Study region: Dongting Lake, Southern China. Study focus: Lakes play a crucial role in Sustainable Development Goal (SDG) 6, which focuses on water-related ecosystems. Here, we devised a methodology to estimate Dongting Lake water storage and analyze their dynamic changes for monitoring SDG 6.6.1 from 2001 to 2020. This study not only provide a geospatial perspective for monitoring water storage for SDG 6.6.1 under the climate oscillations and human impacts in a large floodplain lake but also provide an important scientific basis for improving the optimal allocation of water resources of the Dongting Lake area. New hydrological insights: Remote sensing data are preferable for establishing water storage models during dry seasons, whereas water level is more reliable during wet seasons. Over the past 20 years, average annual water storage in the lake regions has displayed relatively stable fluctuations with an upward trend since 2015. During the wet season, East Dongting Lake has the largest storage capacity, while most of the water resources are concentrated in South Dongting Lake during the dry season. The water storage deviation reached up to 20 %, with a notable negative deviation of more than 10 % during 2011–2015 caused by a severe drought. Related to the stable operation of the Three Gorges Project and the conservation policy initiated by the Chinese government, Dongting Lake is in a stable and recovery period.